Habitat fragmentation increases the risk of local extinction of small reptiles: A case study on Phrynocephalus przewalskii - Cui Yang; Yue Qi; Jiayuan Guo; Liangfei Peng; Neng Xiong; Wenya Zhang; Wei Zhao (Ecotoxicology and Environmental Safety)
Habitat fragmentation represents a multifaceted global conservation threat, exerting both direct and indirect effects on individual animals and communities. Reptiles, particularly smaller species with limited migratory abilities, are especially vulnerable to these changes. This study examines how small reptiles adapt their life history strategies in fragmented habitats and determines whether their responses are primarily due to phenotypic plasticity or genetic adaptation. We focused on Phrynocephalus przewalskii, analyzing body size, reproductive strategies, genetic structure, and diversity across three habitats with varying degrees of fragmentation. This study investigated the response of P. przewalskii to varying degrees of habitat fragmentation in Wuhai City, Inner Mongolia. The study compared morphological characteristics, reproductive investment, genetic diversity, and fluctuating asymmetry of P. przewalskii individuals from the sampling areas. Results showed that individuals in highly fragmented areas exhibited smaller body size, higher reproductive investment, and lower genetic diversity. Genomic analyses revealed significantly fewer SNPs, INDELs, and SVs in the highly fragmented area compared to others, with the slowest linkage disequilibrium decay rate, indicating strong environmental pressure. Furthermore, individuals in the highly fragmented area had significantly higher fluctuating asymmetry, serve as an important ecological and biological indicator reflecting habitat fragmentation. These findings demonstrated that habitat fragmentation negatively impacts the survival and reproduction of P. przewalskii, reducing its genetic diversity and adaptive potential, and increasing the risk of local extinction. This study provides crucial data for understanding the mechanisms of animal adaptation to fragmented habitats and aids in assessing species extinction risks and developing conservation strategies.